Evaluasi Pengelolaan Lansekap Monumen Puputan Klungkung sebagai Tapak Bersejarah - SUKENDAR, NI MADE CLASSIA; SUGIANTHARA, A.A. GEDE; UTAMI, NI WAYAN FEBRIANA (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017DO - 10.24843/JAL.2017.v03.i02.p02, 2017)
The landscape of Puputan Klungkung Monument is a historical site which doesn’t have optimal managemet therefore it is necessary an evaluation on landscape management of the site. The purpose of this research was to discover the pertinent concept of landscape management in Puputan Klungkung Monument applied by the Department of Cultural and Tourism of Klungkung District as well as to provide recommendations in order to improve the site. The research method used were field survey with observation, interviews, questionnaires and literature study technic. Results showed that the solution consist of the main and supporting recommendations. The main recommendations was spatial management for Puputan Klungkung Monument such as recommendation on space, circulation and vegetation. In addition, the supporting solutions was biophysical (facilities and maintenance improvement), cultural and social (effectiveness and service improvement, preparing tour packages), policy (to establish a specialized management agency, to compose Standard Operating Procedure of Puputan Klungkung Monument), and also economic (to use electronic card for entrance ticket). It can be concluded that the management implementation of monument was achieved as much as 80% based on Tupoksi. Hence, it was important to establish a specialized management agency to compose SOP of Puputan Klungkung Monument.